A Novel Approach to Study Cranial Shape in Children with Normal and Sagittal Synostosis: An Application of Geometric Morphometrics - Tadashi MIYAGAWA; Akira YAMAURA (Neurologia Medico-Chirurgica, 2025)
To provide appropriate treatment, neurosurgeons and pediatricians must understand the chronological changes of the cranial morphology in normal children and the differences between normal and sagittal synostosis children. However, this issue has remained unresolved due to the traditional methods of analyzing cranial morphology. Therefore, we applied a new and precise method, geometric morphometrics, to understand cranial morphology in children with normal and sagittal synostosis. This study analyzed morphological differences in the cranium of 30 control children and 14 children with sagittal synostosis using geometric morphometrics and the landmark method on the lateral view of the three-dimensional computed tomography of the skull. The results showed that morphological changes in the cranium of normal children with age could be visualized (p < 0.01), with the parietooccipital and suboccipital areas being the main areas of change. Morphological analysis revealed different cranial morphologies among the control, scaphocephalic sagittal synostosis, and non-scaphocephalic sagittal synostosis groups (p < 0.01), as evidenced by a fan-like spread and reduced cranial height in the sagittal synostosis group compared to the control cranium. Visualization in wireframes could reveal morphological differences, even if small, with statistical differences. This study clarified 3 issues regarding the cranial morphology in normal and sagittal children. The study showed evident age-related differences and changes in the cranial morphology in normal children. Differences in cranial morphologies among the 3 groups were identified. Finally, the study demonstrates that geometric morphometrics is a precise and appropriate method for analyzing morphological differences and changes.